Effects of photodynamic therapy mediated by emodin in cervical carcinoma cells - Galiardi-Campoy, Ana Emília Brumatti [UNESP]; Machado, Francielly Cristina [UNESP]; Carvalho, Tamara [UNESP]; Tedesco, Antonio Claudio; Rahal, Paula [UNESP]; Calmon, Marilia Freitas [UNESP] (Elsevier, 2021)
Cervical cancer is a worldwide public health problem, and improved selective therapies and anticancer drugs are urgently needed. In recent years, emodin has attracted considerable attention due to its anti-inflammatory, antineoplastic, and proapoptotic effects. Furthermore, emodin may be used as a photosensitizing agent in photodynamic therapy. Interest in photodynamic therapy for cancer treatment has increased due to its efficiency in causing tumor cell death. This study aimed to analyze the effect of emodin combined with photodynamic therapy in cervical carcinoma cell lines. At first, emodin presented cytotoxicity in concentration and time-dependent manners in all the specific cell lines analyzed. SiHa, CaSki, and HaCaT cancer cells presented more than 80% cell viability in concentrations below 30 µmol/L. Fluorescence microscopy images showed efficient cellular uptake of emodin in all analyzed cell lines. A significant decrease in cell viability was observed in SiHa, CaSki, and HaCaT cell lines after treatment of emodin combined with photodynamic therapy. These decreases were accompanied by increased ROS production, caspase-3 activity, and fluorescence intensity of autophagic vacuoles. This suggests increased ROS production led to cell death by apoptosis and autophagy. Additionally, after the combination of emodin and photodynamic therapy in SiHa cells, we observed the overexpression of 22 target genes and downregulation of two target genes of anti-cancer drugs. These results show the promising potential for applications that combine emodin with photodynamic therapy for cervical cancer treatment.
Keywords: Apoptosis; Autophagy; Cervical cancer; Emodin; Gene expression; Photodynamic therapy